Analysis of fungal diversity in the feces of Arborophila rufipectus - Ma, Xiaoping; Li, Junshu; Li, Zhiguo; Chen, Benping; Ling, Zhenwen; Feng, Shenglin; Zhong, Zhijun; Peng, Guangneng; Wang, Ya; Jiang, Yaozhang; Gu, Yu (Frontiers in Veterinary Science, 2024)
BackgroundIntestinal fungal composition plays a crucial role in modulating host health, and thus is of great significance in the conservation of endangered bird species. However, research on gut fungal composition in birds is limited. Therefore, in this study, we aimed to examine gut fungal community and potential fecal pathogen composition in wild Arborophila rufipectus.MethodsFecal samples were collected from the habitats of wild A. rufipectus and Lophura nycthemera (a widely distributed species belonging to the same family as A. rufipectus) in summer and autumn. Thereafter, RNA was collected and the internal transcribed spacer rRNA gene was sequenced via high-throughput sequencing to investigate seasonal variations in intestinal core fungi, microbial fungi, and potential pathogenic fungi.ResultsThe gut microbiota of A. rufipectus and L. nycthemera were highly similar and mainly consisted of three phyla, Ascomycota (58.46%), Basidiomycota (28.80%), and Zygomycota (3.56%), which accounted for 90.82% of the fungal community in all the samples. Further, the predominant genera were Ascomycota_unclassified (12.24%), Fungi_unclassified (8.37%), Davidiella (5.18%), Helotiales_unclassified (2.76%), Wickerhamomyces (1.84%), and Pleosporales_unclassified (1.14%), and the potential fecal pathogens identified included Candida, Cryptococcus, Trichosporon, and Malassezia.ConclusionOur results provide evidence that the diversity of intestinal fungi in the endangered species, A. rufipectus, is similar to that in the common species, L. nycthemera, and may serve as a basis for monitoring the status of A. rufipectus and for developing conservation measures.